The NFkB activation domain is 14-amino-acid-long variant of the 9aaTAD - Houser, Josef; Jendruchova, Kristina; Knight, Andrea; Piskacek, Martin (Biochemical journal (London. 1984), 2023)
The nine-amino-acid transactivation domains (9aaTAD) was identified in numerous transcription factors including Gal4, p53, E2A, MLL, c-Myc, N-Myc, and also in SP, KLF, and SOX families. Most of the 9aaTAD domains interact with the KIX domain of transcription mediators MED15 and CBP to activate transcription. The NFkB activation domain occupied the same position on the KIX domain as the 9aaTADs of MLL, E2A, and p53. Binding of the KIX domain is established by the two-point interaction involving 9aaTAD positions p3-4 and p6-7. The NFkB primary binding region (positions p3-4) is almost identical with MLL and E2A, but secondary NFkB binding region differs by the position and engages the distal NFkB region p10-11. Thus, the NFkB activation domain is five amino acids longer than the other 9aaTADs. The NFkB activation domain includes an additional region, which we called the Omichinski Insert extending activation domain length to 14 amino acids. By deletion, we demonstrated that Omichinski Insert is an entirely non-essential part of NFkB activation domain. In summary, we recognized the NFkB activation domain as prolonged 9aaTAD conserved in evolution from humans to amphibians.
Keywords: aminokyseliny; transkripční faktory; aktivace transkripce; vazba proteinů; Protein Binding; lidé; sekvence aminokyselin; Humans; Transcription Factors; nádorový supresorový protein p53; Amino Acids; Amino Acid Sequence; NF-kappa B; Tumor Suppressor Protein p53; Transcriptional Activation